Toward a Feminist Theory of Disability - Wendell, Susan (Hypatia, 1989)
We need a feminist theory of disability, both because 16 percent of women are disabled, and because the oppression of disabled people is closely linked to the cultural oppression of the body. Disability is not a biological given; like gender, it is socially constructed from biologically reality. Our culture idealizes the body and demands that we control it. Thus, although most people will be disabled at some time in their lives, the disabled are made "the other," who symbolize failure of control and the threat of pain, limitation, dependency, and death. If disabled people and their knowledge were fully integrated into society, everyone's relation to her/his real body would be liberated.
Keywords: 1900-1999; 1980-1989; EDI; approches et analyses; bioéthique; care; corps; cours; discipline; intersectionnalité; philosophie; premier cycle; périodes historiques; ressource en ligne; santé; sciences humaines; sex1911; sex1920; thématiques; éthique; études critiques du handicap

La Femme gelée - Ernaux, Annie (Gallimard, 1981)
Professeure de trente ans, mariée à un cadre, mère de deux enfants, elle habite un appartement agréable. Pourtant, c'est une femme gelée. C'est-à-dire que, comme des milliers d'autres femmes, elle a senti l'élan, la curiosité, toute une force heureuse présente en elle se figer au fil des jours entre les courses, le dîner à préparer, le bain des enfants, son travail d'enseignante.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; care; corps; corps féminin; cours; discipline; europe; famille; france; justice sociale; lit301N; littérature; maternité; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; écriture des femmes*